(untitled) (Eurasian Journal of Learning and Academic Teaching, 2026)
This paper presents the author’s concept of the systematic integration of digital educational resources into the training process of specialists in the transport sector of the Republic of Uzbekistan. Digitalization is considered not as an auxiliary tool, but as a key factor in the formation of a holistic digital professional environment that transforms the structure of competency-based training. A multi-level model has been developed, including institutional, methodological, technological, and evaluative-reflective components. An experimental study using statistical methods confirmed a significant increase in the level of professional competencies and the formation of a stable digital professional identity among students.